Strategi Promosi Perekrutan Siswa Di SMK Bisnis Dan Teknologi Terhadap Minat Siswa Untuk Mendaftar - Tjipto Djuhartono; Khoirul Umam; Ai Annisa Utami (RELASI : JURNAL EKONOMI, 2019)
This research concerns students' interest in deciding to enroll in Business and Technology Vocational Schools in terms of factors that influence students from information obtained through promotional media used by Vocational Business and Technology namely Banners, Brochures, Presentations, Friend Recommendations, Parent Choices , Own Choices, Teacher Recommendations and Others. The purpose of this research is to determine what strategies must be done by the Vocational Business and Technology through the promotional media used. The results of the 60 respondents showed that from eight sources of information about the Business and Technology Vocational Schools obtained by these students, the Brochure ranked first, followed by Parent Choices and then Friend Recommendations. The research method used is a survey using a questionnaire. The data obtained is then analyzed and presented in the form of tabulations.